Cognitive Symptom Management and Rehabilitation Therapy (CogSMART) for Traumatic Brain Injury. Treatment manual (ukrainian version). 3rd part: sessions 9-12 - Twamley Елізабет; Noonan Сара; Savla Ґаурі; Schiehser Дон; Jak Емі; Ukrainska Яна; Komova Жанна; Osadchyi Артем; Chaban Олег; Khaustova Олена; Assonov Дмитро (Psychosomatic Medicine and General Practice, 2021)
CogSMART is a cognitive training program for people with traumatic brain injury (TBI). It aims to improve the skills of perspective memory, attention, executive functions (problem solving, planning, cognitive flexibility) in order to more successfully perform daily activities and achieve personal, work and study goals. CogSMART is based not on a large number of trainings and tasks, but on a compensatory cognitive training — improving cognitive skills by using certain adaptation strategies and removing obstacles. The use of CogSMART has already shown good results in the cognitive rehabilitation of people with traumatic brain injury in the United States. The translation of the manual was performed by specialists of the Kyiv City Clinical Hospital for War Veterans with further scientific editing of the text by professors of the Department of Medical Psychology, Psychosomatic Medicine and Psychotherapy at Bogomolets National Medical University. With the permission of Dr. Elizabeth Twamley, the author of the original program, the Ukrainian version of the manual is published in the journal and is available for Ukrainian-speaking audience. The program contains 12 sessions. Sessions 1-4 can be found in the first part of the translated manual via this link. Sessions 5-8 can be found in the second part of the translated manual via this link. This part of the Ukrainian version of the manual presents sessions 9-12 of the CogSMART program. The 9th session is dedicated to learning and memory, is a logical continuation of the 8th session. Participants can learn about new memorization strategies and practice them during group tasks. Session 10 is dedicated to problem solving and cognitive flexibility. Participants will be able to get acquainted with brainstorming strategies and a six-step method of solving problems. The 11th session is a logical continuation of the 10th session and is also dedicated to problem solving and cognitive flexibility. Participants will have the opportunity to learn verbal strategies, hypothesis testing and other skills that will be helpful during planning activities. The 12th session is the final one, during which the results of the CogSMART sessions are summed up and further perspectives and ways of development are discussed.